Ammonium Content Determination by Different Analytical Methods in the Manure with Different Additives and Its Change During Storage - Irmantas Parašotas; Violeta Juškienė; Alvyra Šlepetienė; Gitana Kadžienė (Agriculture)
Ammonium (NH4+) content is one of the most important parameters in manure assessment. The accurate and rapid determination of this inorganic form of nitrogen is therefore important not only in agronomy, when calculating fertilizer application rates, but also in scientific studies, for example, in the study of greenhouse gas emissions from stored manure. There is not enough research to assess which analytical method is the most appropriate for the determination of (NH4+) in manure with additives such as perlite, vermiculite, or peat. We compared three analytical methods for NH4+ determination: distillation, ionometry, and spectrophotometry. The results showed that the distillation method had the lowest average coefficient of variation (Cv) between the two laboratory replicates, with a Cv = 0.77%, while the ionometry and spectrophotometry methods had average Cv values of 1.83% and 3.97%, respectively. A lower coefficient of variation indicates that the analytical method is less sensitive to various interferences, resulting in more reliable data. Experimental data also show that storing manure for 40 days reduces the NH4+ content from about 21,000 ppm to about 7000 ppm and that the use of additives such as perlite, vermiculite, or peat did not significantly affect NH4+ retention compared with control samples (without additives). Based on the results of our study, we recommend using the distillation method for the determination of NH4+ in the manure with additives in agrochemical and scientific laboratories.